Penggambaran Solidaritas Gangster Pada Film "High And Low The Worst X Cross” Di Netflix - Balfagih, Muhammad Zulfan; Agustrijanto, Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Solidarity in gangster organizations is demonstrated in a variety of different behaviors. The aim of this research is to reveal solidarity between gangsters in the feature film "High and Low The Worst X Cross" and relate it to the theory of Social Reality Construction Theory in Mass Media. This research method uses Charles Sander Pierce's semiotic analysis method using three stages of sign, object and interpretant analysis. The results of this research found that gangsters are faced with a bad image by society and always have a negative impact on society. The existence of a view from the community makes the personality of the gangster organization become worse and difficult to control. During the analysis of signs, objects, and interpretants, it was found that gangster organizations, apart from having a bad view, were always seen in the eyes of society. Therefore, gangster organizations hide their character in society and do not display their solidarity